Alginate Oligosaccharide DP5 Exhibits Antitumor Effects in Osteosarcoma Patients following Surgery - Chen, Jiayu; Hu, Yu; Zhang, Lirong; Wang, Yingjian; Wang, Shichao; Zhang, Yanzi; Guo, Haiyan; Ji, Degang; Wang, Yingtao (Frontiers in Pharmacology, 2017)
Osteosarcoma is a malignant musculoskeletal tumor that has high-rate morbidity and mortality worldwide. Alginate oligosaccharide (AOS), a natural product, has antitumor activities and may have therapeutic effects in osteosarcoma, the molecular mechanisms of which remain unclear. AOS was prepared from alginate sodium using alginate lyase. The fractions of AOS were further isolated by size-exclusion chromatography and verified by electrospray ionization mass spectrometry (ESI-MS). Osteosarcoma patients were enrolled in the study and assigned into two groups: AOS (AG, oral administration of 10-mg AOS daily) and control groups (CG, placebo). Preoperative and postoperative clinical data were investigated and analyzed. Four different degrees of polymerizations (DPs) were isolated and denominated as DP2, DP3, DP4 and DP5. Among these polymers, only DP5 showed antitumor functions on osteosarcoma cells. Before surgery and the outcome of primary end point after surgery, no significant differences were observed for clinical data and tumor size between the AG and CG groups (P > 0.05). After two-year therapy, the mean tumor volume was 214.6 ± 145.7 c.c. in AG and 467.2 ± 225.3 c.c in CG (P < 0.01). The rate of local recurrence was 44.9% and 68.7% in AG and CG, respectively (P < 0.01). AOS treatment resulted in the increase in serum levels of SOD, GSH, HDL-C and reduction in the levels of interleukin-1 (IL-1) beta and IL-6; the ratios of AST/ALT; and triglycerides, total cholesterol, low-density lipoprotein cholesterol LDL-C and malondialdehyde (MDA) (P < 0.05). AOS reduces osteosarcoma progression, which is associated with improvement in antioxidant and anti-inflammatory capacities of patients, and may be used as a potential drug for osteosarcoma therapy.